A Method for Estimating Micro-area Composition of Quartz-diorite Based on Quantitative Mapping of Electron Probe Microanalysis - HU Yaoyao; WANG Haozheng; HOU Yuyang; SONG Haoran (Yankuang ceshi, 2022)
BACKGROUND The estimation of bulk composition of the micro-area of a rock is an important basis of tracing rock evolution. The conventional electron probe microanalysis (EPMA) mapping method cannot provide quantitative analysis results of the surface scanning area. OBJECTIVES In order to estimate the composition of the micro-area by quantitative mapping of EPMA. METHODS The mapping and point analyses were carried out to determine the composition of the micro-area of a homogeneous quartz-diorite. By performing image correction of the pixels of the mapping of the major elements, and using the point analysis data after ZAF correction and the gray value of the surface scan image to perform the least square curve fitting method, the X-ray intensity and concentration were converted. RESULTS By comparing to X-ray fluorescence spectrometry (XRF), the relative errors of SiO2, CaO, FeO, Al2O3 and TiO2 of EPMA method were within 10%, and the relative standard deviation was less than 10%. The relative error and standard deviation of MgO and Na2O were slightly larger, which can be improved by multiple measurements. The K2O content were not accurate due to lack of K-rich silicate minerals' point analysis. CONCLUSIONS The results show that the estimation of micro-area composition of a rock with relatively homogeneous mineral distributions can be carried out by using point analyses of EPMA to correct the mapping under good instrument conditions, and the influence of mineral morphology, particle size, and distribution can be reduced by multiple measurements on different sections.